Dental eruption in East African wild chimpanzees. Issue 82 (May 2015) - Machanda, Zarin; Brazeau, Nick F.; Bernard, Andrew B.; Donovan, Ronan M.; Papakyrikos, Amanda M.; Wrangham, Richard; Smith, Tanya M.
Abstract: Knowledge of chimpanzee development has played an essential role in our understanding of the evolution of human ontogeny. However, recent studies of wild ape dentitions have cast doubt on the use of developmental standards derived from captive individuals. Others have called into question the use of deceased wild individuals to infer normative development. We conducted a high resolution photographic study of living known-age subadults in the Kanyawara community (Kibale National Park, Uganda) to generate a comprehensive three year record of dental eruption (including tooth emergence ages). These non-invasive data allow comparisons of captive and wild chimpanzees, establish accurate developmental standards for relatively healthy wild individuals, and facilitate direct assessments of primate-wide associations between dental development and life history. Emergence ages in the Kanyawara chimpanzees are very similar to living Gombe chimpanzees, and are broadly comparable to deceased Taï Forest chimpanzees. Early-emerging teeth such as the deciduous dentition and first molar (M1) appear during a time of maternal dependence, and are almost indistinguishable from captive chimpanzee emergence ages, while later forming teeth in the Kanyawara population emerge in the latter half of captive age ranges or beyond. Five juveniles whose lower M1s emerged by or before 3.3 years of age continued to nurse for a year or more beyond M1 emergence, and their mothers showed considerable variation in reproductive rates. The third molars of two adolescent females emerged several months to several years prior to the birth of their first offspring. Given that broad primate-wide relationships between molar emergence and life history do not necessarily hold within this population of chimpanzees, particularly for variables that are reported to be coincident with molar emergence, we suggest that further study is required in order to predict life history variables in hominins or hominoids.